The anti-depression effect of Xylaria nigripes in patients with epilepsy: A multicenter randomized double-blind study. (July 2015) - Peng, Wei-Feng; Wang, Xin; Hong, Zhen; Zhu, Guo-Xing; Li, Bing-Mei; Li, Ze; Ding, Mei-Ping; Geng, Zhi; Jin, Zheng; Miao, Ling; Wu, Li-Wen; Zhan, Shao-Kang
Highlights: Treatment for comorbid depression in patients with epilepsy is still challenging. Randomized clinical trials and new therapies are needed for patients with comorbidity of epilepsy and depression. Xylaria nigripes can alleviate depressive symptoms with 12 weeks treatment and is well tolerated by patients with epilepsy. Abstract: Purpose: The comorbidity of depression in patients with epilepsy is common and treatment is still controversial. This pilot study was aimed at evaluating the efficacy and safety of Xylaria nigripes for treating depressive symptoms in patients with epilepsy during 12 weeks of treatment. Methods: A multicenter, double-blind, placebo-controlled, randomized superiority study was performed. A total of 104 patients with epilepsy who fulfilled the study criteria were randomized 1:1 to receive Xylaria nigripes (the Wu Ling group) or placebo (the placebo group) treatment in the 12-week period of study. The participants were visited on weeks 0, 2, 4, 8, and 12 of the treatment course. Results: Eighty-one patients finished all of the visits. The primary efficacy endpoint in this study was the total effective rate for depression, which was significantly greater in the Wu Ling group (51.3%, n  = 39) than in the placebo group (35.7%, n  = 42, 0.51–0.36 = 0.15, 95% CI −0.06 to 0.37, U  = 2.83, P  = 0.002) after 12 weeks of treatment. No differences in seizure frequency or changes in severity were found between the Wu Ling and the placebo groups. In addition, the quality of life and seizure worry subscale scores in patients with epilepsy were also improved more notably in the Wu Ling group than in the placebo group ( P  < 0.05). Most of the adverse effects (AEs) in this study were mild and had no differences between the Wu Ling and the placebo groups. Conclusion: Xylaria nigripes could alleviate depressive symptoms within 12 weeks treatment and was well tolerated in patients with epilepsy.